Identification of the Secondary Metabolites and Characterization of Lagerstroemia Loudonii T. & B. - Faramayuda, Fahrauk; Hermanto, Faizal; Windyaswari, Ari Sri; Riyanti, Soraya; Nurhayati, Viola Aditya (Journal of Islamic Pharmacy, 2021)
Bungur  (Lagerstroemia loudonii T. B) is a type of plant widely grown in Indonesia and can be found in teak forests, mixed forests, and is found as ornamental plants or protective trees on the roadside. In the fruit section, Lagerstroemia loudonii is used as antituberculous and antimalarial. On the bark, the part is used as antidiarrheal. Based on some parts of the Lagerstroemia loudonii  plants' activity data, this plant has the potential to be developed into traditional medicine. Standardized traditional medicine material is necessary to identify efficacious compounds and characterization in some parts of Lagerstroemia loudonii. The purpose of this research is to develop Lagerstroemia loudonii into traditional herbal medicine or standardized herbal medicine. Identification of efficacious compounds and characterization of crude leaf drugs, bark, stems, and fruit of Lagerstroemia loudonii. The phytochemical screening phase of the crude drugs of leaves, bark, stems, and fruit ofLagerstroemia loudonii against includes examining alkaloids, flavonoids,  quinones, tannins, polyphenols, saponins, steroids and triterpenes, monoterpenoids and sesquiterpenoids. The determination of the characteristics of raw material carried out includes nonspecific parameters. Nonspecific parameters are the determination of total ash content, water-soluble ash content, acid insoluble ash content. each experiment was carried out three times and calculated the average yield and deviation.  Identification results of the class of efficacious compounds in some parts of the Lagerstroemia loudonii  plant are on the leaves and fruits containing alkaloids, flavonoids, saponins, quinones, tannins, polyphenols, monoterpenoids, and sesquiterpenoids as well as steroids and triterpenoids. At the bark and stem, the bark contains alkaloids, flavonoids, saponins, quinones, tannins, polyphenols, monoterpenoids, and sesquiterpenoids. Characterization results of Lagerstroemia loudonii  leaf extract total ash content 4.45 ± 0.30% w/w, water-soluble ash content 4.08 ± 0.27% w/w, acid insoluble ash content 0.59 ± 0.06% w/w, the extract specific gravity was 0.59 ± 0.063. Lagerstroemia loudonii  stem bark extract, total ash content 1.94 ± 0.12% w/w, water-soluble ash content 1.47 ± 0.03% w/w, acid insoluble ash content 0.24 ± 0.02% w/w, the extract specific gravity is 0.82 ± 0.01. Lagerstroemia loudonii  stem extract, total ash content3.18 ± 0.16% w/w, water-soluble ash content 2.36 ± 0.38% w/w, acid insoluble ash content 0.43 ± 0.07% w/w, extract specific grafity 0.81 ± 0.01. Lagerstroemia loudonii  fruit extract, total ash content 11.45 ± 1.16%w/w, water-soluble ash content 10.1 ± 1.49% w/w, acid insoluble ash content 1.46 ± 0.88% w/w,extract specific grafity 0.81 ± 0.01. Based on phytochemical screening data and the characterization of bungur plants potential to be developed into raw materials for traditional medicineKeywords: Lagerstroemia loudonii, secondary metabolite, raw material characterization